2018
DOI: 10.1063/1.4999944
|View full text |Cite
|
Sign up to set email alerts
|

Space environment simulation and sensor calibration facility

Abstract: The Mumbo space environment simulation chamber discussed here comprises a set of tools to calibrate a variety of low flux, low energy electron and ion detectors used in satellite-mounted particle sensors. The chamber features electron and ion beam sources, a Lyman-alpha ultraviolet lamp, a gimbal table sensor mounting system, cryogenic sample mount and chamber shroud, and beam characterization hardware and software. The design of the electron and ion sources presented here offers a number of unique capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Under microgravity conditions, the e cacy of antibiotics decreases and the mutation rate of microorganisms increases signi cantly [2,3]. Assuming that there is no obvious microbial contamination in the structure of the spacecraft or its air, food, and water supply, any infection of the crew members will be caused by endogenous human and animal ora carried at the time of departure, which may limit the types of infection encountered in a predictable manner [4,5]. It is reported that the micro ora of bacteria was found after a short ight, which may be related to diet, mainly intestinal micro ora, such as Escherichia coli (E. coli) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Under microgravity conditions, the e cacy of antibiotics decreases and the mutation rate of microorganisms increases signi cantly [2,3]. Assuming that there is no obvious microbial contamination in the structure of the spacecraft or its air, food, and water supply, any infection of the crew members will be caused by endogenous human and animal ora carried at the time of departure, which may limit the types of infection encountered in a predictable manner [4,5]. It is reported that the micro ora of bacteria was found after a short ight, which may be related to diet, mainly intestinal micro ora, such as Escherichia coli (E. coli) [6,7].…”
Section: Introductionmentioning
confidence: 99%